200.000 IU of vitamin D does not reduce resting Blood Pressure and Inhibit Post-Exercise Hypotension in elderly women: a pilot study - GONÇALVES,MARIA DA CONCEIÇÃO R. (2020)
Abstract Given the scarcity of studies with elderly and the existence of studies investigating the effect of vitamin D supplementation in PEH (post exercise hypotension), this study evaluated the effect of a single megadose of vitamin D on resting blood pressure (RBP) and post-exercise hypotension (PEH) in the elderly. 11 hypertensive elderly women (70.3 ± 1.7 years) received a single megadose of 200.000 IU of cholecalciferol or a placebo, orally, through capsules. On day 7, the subjects performed 30 minutes of aerobic exercise with blood pressure measurement before exercise and every 10 minutes after exercise during 60 minutes, besides cardiac autonomic modulation. RBP did not significantly change. Exercise promoted significant systolic PEH only in one moment post exercise in treated group and in the placebo group promoted significant systolic PEH at four moments. Significant diastolic PEH did not occur in any of the groups. Sympathovagal activity increased at post exercise balance in supplemented subjects at 20 min, 40 min, 50 min and 60 min when compared to rest; this increase was not observed in the placebo. A megadose of vitamin D did not reduce RBP, promoted partial inhibition of systolic PEH and increased sympathovagal balance.